Pengaruh Model Pembelajaran Direct Intruction Menggunakan Peching PAD terhadap Hasil Belajar Tendangan Sabit pada Siswa Kelas IX SMP Negeri 2 Sruweng Kabupaten Kebumen - Mokhamad Parmadi; Ahmad Saeifudin Zuhri (Journal on Education, 2024)
Pencak silat is a game (skill) in defending oneself with the skill of parrying, attacking and defending oneself, either with or without weapons. Student interest in learning at SMP 2 Sruweng Kebumen regarding pencak silat learning material is lacking. This is because the Pencak Silat Martial Arts subject, in its application, always uses the lecture method every time in the learning process, this causes less development of learning abilities and individual development so that learning abilities decrease. The learning model tested in this research is the Direct Instruction learning model using Peching Pad. This research aims to find out how much influence the Direct Instruction learning model using Peching Pad has on the learning outcomes of pencak silat crescent kicks in class IX students of SMP Negeri 2 Sruweng, Kebumen Regency in 2024. This research is an experimental research with a one group pretest-posttest design. The population of this study was male students in class IX of SMP Negeri 2 Sruweng, Kebumen Regency. The sampling used was purposive sampling. Class IX A boys and is the class created the experimental class consisted of 28 students. The instrument used in this research is a test used to measure the ability of pencak silat front kick technique skills. Data analysis uses the t test. The research results are as follows, the t-test results obtained a value of tcount > ttable (13.104 > 2.05) at a significance level of 5%. So it can be concluded that there is a significant difference between the pretest and posttest. If we look at the mean difference figure of 16.97, this shows that the Direct Instruction learning model using Peching Pad provides a change in the results of pencak silat sickle kicks, namely 16.97 more than before the learning was given with an increase of 26.69%. The Direct Instruction learning model using Peching Pad has an influence on learning outcomes for pencak silat sickle kicks. The conclusion from the research results is that there is a significant influence of the Direct Instruction learning model using Peching Pad on learning outcomes for sickle kicks with a percentage of 26.69%. For this reason, the Direct Instruction learning model using Peching Pad is influential and needs to be implemented so that the results of learning the Pencak Silat sickle kick are maximized. The abstract should be clear, concise, and descriptive. This abstract should provide a brief introduction to the problem, objective of paper, followed by a statement regarding the methods and a brief summary of results. The abstract should end with a comment on the significance of the results or a brief conclusion. Abstracts are written in 10pt Times New Roman, preferably not more than 200 words